2012
DOI: 10.1128/mbio.00285-11
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Sigma Factor-Like Regulator RpoQ Controls Luminescence, Chitinase Activity, and Motility in Vibrio fischeri

Abstract: Vibrio fischeri, the bacterial symbiont of the Hawaiian bobtail squid, Euprymna scolopes, uses quorum sensing to control genes involved in bioluminescence, host colonization, and other biological processes. Previous work has shown that AinS/R-directed quorum sensing also regulates the expression of rpoQ (VF_A1015), a gene annotated as an RpoS-like sigma factor. In this study, we demonstrate using phylogenetics that RpoQ is related to, but distinct from, the stationary-phase sigma factor RpoS. Overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
3
37
0
Order By: Relevance
“…These are annotated as putative lipoproteins, response regulators, a sigma factor, and an antisigma factor antagonist (40). The sigma factor RpoQ (VSAL_II0319) was recently described in V. fischeri and found to be regulated by QS (53). Of the Vibrionaceae, only V. salmonicida and V. fischeri encode this sigma factor, and in both species LitR positively regulates rpoQ expression.…”
Section: Discussionmentioning
confidence: 99%
“…These are annotated as putative lipoproteins, response regulators, a sigma factor, and an antisigma factor antagonist (40). The sigma factor RpoQ (VSAL_II0319) was recently described in V. fischeri and found to be regulated by QS (53). Of the Vibrionaceae, only V. salmonicida and V. fischeri encode this sigma factor, and in both species LitR positively regulates rpoQ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential and multitiered quorum sensing regulatory networks have been described for several proteobacterial strains, including Vibrio fischeri, in which quorum sensing is used to modulate intermediate and late symbiotic colonization of the Euprymna scolopes light organ and bioluminescence (12,17,65,66). V. fischeri has two AHL-based quorum sensing systems that synthesize different AHLs at different stages of squid colonization (12,17,65).…”
Section: Discussionmentioning
confidence: 99%
“…V. fischeri has two AHL-based quorum sensing systems that synthesize different AHLs at different stages of squid colonization (12,17,65). Moreover, it has been shown that the response regulator that directly controls bioluminescence (LuxR) can respond to the two AHLs at different binding efficiencies, thus inducing bioluminescence at different cell densities and stages of colonization (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of chitin by vibrios involves multiple levels of gene regulation that govern motility, chemotaxis, extracellular polysaccharide and biofilm matrix protein synthesis and secretion, type IV pilus production, chitin-binding protein secretion, chitin surface attachment, biofilm formation, extracellular chitinase secretion, chitoporin expression, and competence (166,338,470,(520)(521)(522)(523). Association with insoluble materials may be the preferred lifestyle of vibrios, including deep-sea hydrothermal vent species (15,403,524), and regulatory systems involving TCSs, chemotaxis, QS, sRNAs, cAMP, c-di-GMP, alternative sigma factors, and the stringent response enable vibrios to optimize resource utilization and survival (Fig.…”
Section: An Example Of Microbial Interaction With Surfaces: Vibrio Chmentioning
confidence: 99%